The green tea catechin epigallocatechin gallate (EGCG) blocks cell motility, chemotaxis and development in Dictyostelium discoideum. - Kyle J McQuade (Public Library of Science (PLoS), 2013)
Catechins, flavanols found at high levels in green tea, have received significant attention due to their potential health benefits related to cancer, autoimmunity and metabolic disease, but little is known about the mechanisms by which these compounds affect cellular behavior. Here, we assess whether the model organism Dictyostelium discoideum is a useful tool with which to characterize the effects of catechins. Epigallocatechin gallate (EGCG), the most abundant and potent catechin in green tea, has significant effects on the Dictyostelium life cycle. In the presence of EGCG aggregation is delayed, cells do not stream and development is typically stalled at the loose aggregate stage. The developmental effects very likely result from defects in motility, as EGCG reduces both random movement and chemotaxis of Dictyostelium amoebae. These results suggest that catechins and their derivatives may be useful tools with which to better understand cell motility and development in Dictyostelium and that this organism is a useful model to further characterize the activities of catechins.